Star Trek : countdown - Johnson, Mike.; Roddenberry, Gene.; Orci, Roberto; Kurtzman, Alex.; Jones, Tim.; Messina (San Diego, CA : IDW Pub., 2009)
A graphic novel that explores the origins of Nero, a villainous "Star Trek" character from Romulan who threatens the sanctity of the entire universe.
"Originally published as Star Trek: Countdown issues #1-4"--T.p. verso.
"Star Trek created by Gene Roddenberry"--T.p. verso.
"Official movie prequel"--Cover p. [4].
Young Adult
Keywords: Spock (Fictitious character) -- Comic books, strips, etc. -- Fiction; Interplanetary voyages -- Comic books, strips, etc. -- Fiction; Life on other planets -- Comic books, strips, etc. -- Fiction; Spock (Fictional character) -- Comic books, strips, etc. -- Fiction; Interplanetary voyages -- Comic books, strips, etc. -- Fiction; Life on other planets -- Comic books, strips, etc. -- Fiction; Science fiction graphic novels; Movie novels; Comic books, strips, etc; Graphic novels; Star Trek fiction; Science fiction comic books, strips, etc; Movie novels; Graphic novels